The impact of fast and short-term weight loss on the hormones and performance of Iranian young elite wrestlers - Eghbal Moghanlou, A.; Salehi, V.; Akalan, C.; Akalan, H. (Sport Science - International Scientific Journal of Kinesiology, 2018)
Purpose: To evaluate the effects of fast weight loss (FWL) and short terms weight loss(SHWL) on the salivary free testosterone and cortisol and performance of young elite wrestlers. Methods: 14 wrestlers (mean age of 17.79 +/- 0.75 years, height of 172.06 +/- 4.61 cm, weight of 70.04 +/- 8.72 kg, and BMI of 23.21 +/- 2.09) who were randomly assigned into two groups: fast-term weight loss group (FWL) (performed exercises with conventional method during 24 hours, with severe food restriction and water and using thick clothing) and short-term weight loss group (SHWL) (performed the exercises in a 10-day program with a daily calorie reduction from 4 to 5% and exercise program included 3 sessions in which each session lasted 40 minutes) participated in this study. Exercise program by weight was also similar in both groups. The salivary free testosterone, cortisol and function indicators were measured in two phases (pre-test and post-test). Results: The results showed that SHWL had no significant impact on hormone and functional variables (p.0.05). Although in the FWL, time of Rockport test improved, causing to reduce aerobic fitness compared to pretest (p.0.05), it had no significant effect on other variables (P.0.05). Also the percentage of inter-group changes showed no significant difference between the groups (P.0.05). Conclusion: SHWL has some advantages over FWL, since it leads to less reduction in functional indices and athletes can participate in competitions with high confidence.